The phenomenon of bullying in junior high school students nowadays - Addini Nurlia; Siti Partini Suardiman (Association for Scientific Computing Electrical and Engineering(ASCEE), 2020)
Bullying is one of the most aggressive attitudes and violence between peers in the school environment. This research aims to determine how the phenomenon of bullying is happening at this time, especially in junior high school students. This research using qualitative methods, data collected by interview techniques. The research subject is counseling guidance teachers at junior high school. The object in this research is one of the junior high school in Yogyakarta. The study's findings are that junior high school students conduct verbal bullying behavior, physical bullying, and cyberbullying. There are several factors of bullying: behavior within seniority, the history of being a victim of bullying, economic status, violence from the media, family, and peer factors. The impact of bullying behavior can be felt for victims and the more bully or people who do the bullying.